DINAMICA REPREZENTĂRII SOCIALE. ROLUL ELEMENTELOR NOI - USM ADMIN (Moldova State University, 2007)
The social representations do not emerge incidentally. They are a result of the way individuals tend to interact with each other or discover the world. Having a limited life time, the mental structures we refer to lack definitively elabo- rated compositional profiles. The alteration of the social representations happens every time individuals come across a new element which endangers their status quo. New elements are usually ideas, norms, values, attitudes, convictions, beliefs, but also behavioral practices which are unfamiliar to what is already known and appreciated. From the moment they appear, they put a growing pressure on the individuals, making them to rally to the new meanings of the time.